Integrating Maqasid al-Shariah into Indonesia’s Mortgage Rights: A Normative Analysis toward Substantive Justice - Masturi, Frida Nurrahma; Inayah, Asti; Wakhid, Nur (Universitas Trunojoyo Madura, 2025)
Mortgage right serves as a form of material security that provides legal certainty and protection for creditors when debtors fail to fulfill their obligations. In Indonesia, however, the implementation of mortgage rights particularly within the Islamic financial system remains grounded in the Indonesian Civil Code, which does not fully reflect the core principles of Islamic law: justice (‘adl), benefit (maslahah), and trust (amanah). This study employs a normative juridical approach to examine the concept of mortgage rights from an Islamic legal perspective and its relevance to land mortgage rights. By exploring the doctrine of rahn and the objectives of maqasid al-shariah, the research reveals that Sharia based mortgage rights emphasize not only legal protection but also ethical responsibility and social balance. Accordingly, their implementation should prioritize sulh (amicable settlement) before execution to ensure substantive justice. The study concludes that incorporating maqasid al-shariah values into Indonesia’s material security law reform can harmonize legal certainty with moral fairness, thereby promoting justice and public welfare.